2007
DOI: 10.1590/s1517-83822007000100036
|View full text |Cite
|
Sign up to set email alerts
|

Serological and genetic diversity amongst Salmonella strains isolated in a salami processing line

Abstract: Salmonella is one of the most important agents of foodborne disease in Brazil and in other countries, with meat and meat products being identified as important vehicles of salmonelosis. A total of 54 Salmonella strains isolated from a commercial salami processing line were first serotyped and then their antibiotic resistance and macro restriction profiles were determined. 11.1% of the strains showed resistance to 3 or more antibiotics with profile AmpCStxTe being the most frequent. PFGE generated 9 and 12 prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…In Brazil, only S. Panama and Salmonella enterica subspecies enterica rough were found in a salami production line in the State of Paraná, with S. Panama being the most frequently detected (Ribeiro et al, 2007). In the present study, these serotypes were detected in the slaughterhouse as environmental contaminants present in the corral, deboning tables and ribbon saw.…”
Section: Resultsmentioning
confidence: 40%
See 2 more Smart Citations
“…In Brazil, only S. Panama and Salmonella enterica subspecies enterica rough were found in a salami production line in the State of Paraná, with S. Panama being the most frequently detected (Ribeiro et al, 2007). In the present study, these serotypes were detected in the slaughterhouse as environmental contaminants present in the corral, deboning tables and ribbon saw.…”
Section: Resultsmentioning
confidence: 40%
“…These strains may display an invasive capacity, a characteristic of multi-resistance to antimicrobial drugs, which are genes encoded capacity that may potentiate their persistence in the organism and hence, their pathogenicity (Ribeiro et al, 2007;Huang et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of pulsedfield gel electrophoresis (PFGE) for assessing genetic diversity of Salmonella isolates and the clonal transmission of isolates has been reported in both the food and livestock industries. In Brazil, some studies have demonstrated the occurrence of S. Panama mainly in water, poultry and swine meat, in foods such as salami, and in the environment, however, there is little information available on the virulence and genetic diversity of S. Panama strains 9,11 .…”
Section: No/yearmentioning
confidence: 99%
“…S. Panama isolates from various origins exhibit antimicrobial resistance, and multidrug-resistant strains are common. In addition, S. Panama infections frequently recur 8,9,10 .…”
mentioning
confidence: 99%